Beyond Cooperative Learning: Jigsaw as an Integrated Learning Management Strategy for Enhancing Learning Quality - Dewi Rokhmah; Moh. Fatir Ainunnajib; Kuswoyo Gumilang (Al-Qalam Institue, 2026)
This study aimed to analyze the implementation of the Jigsaw method as a learning management strategy and examine its contribution to improving learning quality among students in the Islamic Education Management Study Program at STIT Al Hikmah Benda Brebes. A descriptive qualitative approach was employed, involving one lecturer and 18 students. Data were collected through participant observation, in-depth interviews, and documentation during three learning meetings and analyzed using data condensation, data display, and conclusion drawing. The findings revealed progressive improvements in learning quality across student activity, learning motivation, material understanding, and learning outcomes. Evaluation performance increased from 50.0% of students demonstrating responses in the first meeting to 77.8% in the second and 94.4% in the third. The study concludes that systematically managed Jigsaw learning strengthens participation, responsibility, collaboration, confidence, and material mastery. The implication is that Jigsaw can function beyond a cooperative technique as an integrated learning management strategy for promoting active, student-centered, and quality-oriented learning in Islamic higher education.